Solvent suppression in solid‐state DNP NMR using Electronic Mixing‐Mediated Annihilation (EMMA). (4th February 2020) - Ziarelli, Fabio; Thureau, Pierre; Viel, Stéphane; Mollica, Giulia
Abstract: We show here that the Electronic Mixing‐Mediated Annihilation (EMMA) method, previously reported for the suppression of background signals in solid‐state nuclear magnetic resonance spectra, can be successfully applied to remove the solvent signals observed in the case of nuclear magnetic resonance spectra obtained with dynamic nuclear polarization. The methodology presented here is applied to two standard sample preparation methods for dynamic nuclear polarization, namely, glass forming and incipient wetness impregnation. It is demonstrated that the Electronic Mixing‐Mediated Annihilation method is complementary to the different methods for solvent suppression based on relaxation filters and that it can be used to preserve the quantitative information that might be present in the pristine spectra. Abstract : Electronic Mixing‐Mediated Annihilation method can be successfully applied to remove the solvent signals observed in the case of nuclear magnetic resonance spectra obtained with dynamic nuclear polarization. The methodology is demonstrated on two standard sample preparation methods for dynamic nuclear polarization: glass forming and incipient wetness impregnation. Electronic Mixing‐Mediated Annihilation method is complementary to other methods for solvent suppression based on relaxation filters and can preserve the quantitative character of the experiment.